If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = y + -19 Reorder the terms: 15 = -19 + y Solving 15 = -19 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 15 + -1y = -19 + y + -1y Combine like terms: y + -1y = 0 15 + -1y = -19 + 0 15 + -1y = -19 Add '-15' to each side of the equation. 15 + -15 + -1y = -19 + -15 Combine like terms: 15 + -15 = 0 0 + -1y = -19 + -15 -1y = -19 + -15 Combine like terms: -19 + -15 = -34 -1y = -34 Divide each side by '-1'. y = 34 Simplifying y = 34
| x+9.7=16.1 | | 1-X+4X+17=-3X | | (2w-9)(1-w)=0 | | 5x^2=20x | | -15r=9r+1-7r | | X^2+4x+24=0 | | 3x=6y | | 15x^3-6x^2=0 | | 2x^2+24x+64=0 | | 45c+7=39c-26 | | -18=15-(6T+5) | | 2k-16=8 | | -10=-15x-5x | | 9x=36 | | 11(x-1)=5+10x | | 9x+18=36 | | y=15x+15 | | .3x+10=55 | | .33x+10=55 | | x+29=13 | | 9=12x-4x^2 | | -3-8+7t=34+9t-2 | | 12q^2=17q+5 | | 36u=9u^2 | | 5x-(2x+7)=5 | | 132=r^2 | | 25b+11=-6b^2 | | 33+15w=3w-w | | 16h^2=25 | | x^2+6x-91=0 | | 8-3t=5t^2 | | 45.6=6x |